SWHORD simulator: A platform to evaluate energy transition targets in future energy systems with increasing renewable generation, electric vehicles, storage technologies, and hydrogen systems. (15th May 2023) - Sousa, Jorge; Lagarto, João; Carvalho, Ezequiel; Martins, Ana
Abstract: This paper presents the simulation platform SWHORD, specially designed for the analysis of future energy systems under energy transition targets. The model is implemented in GAMS as a cost minimization mixed integer programming problem of a hydro-thermal power system, which includes high penetration of non-dispatchable renewable generation, storage technologies, electric vehicles, and hydrogen systems. Simulations are performed on an hourly basis for one year of operation, enabling the evaluation of both short-term dynamics and the seasonal behaviour of the system and including the hourly power generation profile by technology, fuel and emission costs, CO2 emissions and storage levels, as well as the renewable curtailment needed to balance the system. The model was validated by backtesting with historical data of the Portuguese power system and, from a comprehensive statistical analysis of the dispatchable generation, it is concluded that the simulation results present a good fit with the real data. An illustrative use case is presented to evaluate the consistency of the Portuguese targets for 2030. Simulation results put in evidence the advantages of the SWHORD simulator to study the complex interactions among the new drivers of future energy systems, such as electric vehicles, storage technologies, and hydrogen systems. Highlights: Evolutive version of the power system simulator SWHORD for energy transition analysis. Simulator computes yearly aggregated results and hourly profiles of power generation. Example use case for the Portuguese power system considering hydrogen production. 2030 hydrogen production is partially supplied with an increase in CCGT production.